Rethinking perception and cognition in the digital environment - Kirjakovski, Atanas (Frontiers in Cognition, 2023)
Undoubtedly, the future of humanity is digital. As we transition into this new technological era, we are confronted with many uncertainties. The digital environment, a relatively recent phenomenon, differs both qualitatively and quantitatively from other natural and social environments. Its ubiquity and rapid evolution, along with the ease of automating and replicating digital code, set the stage for significant impacts on human cognition and perception. This article conceptually explores the general characteristics of the digital environment, highlights its significance and relevance to cognitive science, summarizes a range of recent findings on the effects of digital technology on our cognitive and perceptual processes, and concludes with several hypotheses about the evolution of our minds in the digital future.